Peran Tarekat Naqsabandiyah Shafaiyah dalam Pembentukan Karakter pada Jamaah Ponpes Ahlus Shafa Wal Wafa - Ahmad Ainur Ridho; Adi Mohammad Pajar; Fahrul Abil Khadafi (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This research highlights the important role of the Naqsabandiyah Shafaiyah Tarekat in shaping the character of the worshippers at the Ahlus Shafa Wal Wafa Islamic Boarding School. This order centers on the purification of the soul (tazkiyatun nafs), spiritual discipline, and the strengthening of relationships with Allah and fellow humans. The process of character development is carried out continuously through various routine activities, such as dhikr, wirid reading, recitation, and direct guidance from a mursyid. These activities aim to create a deep religious atmosphere to encourage changes in attitudes and behaviors of worshippers. The results showed that after following the tarekat, the pilgrims experienced a significant increase in spiritual, emotional, and social aspects. They become calmer, more patient, and wiser in dealing with life's problems. In addition, the awareness to live simply and stay away from despicable traits such as arrogance and envy is growing along with the routine of dhikr and self-introspection. In the social context, this tarekat also succeeded in fostering an attitude of care, the spirit of mutual cooperation, and responsibility for the surrounding environment. Thus, the Naqsyabandiyah Shafaiyah Tarekat not only functions as a means to get closer to Allah, but also becomes an effective instrument in shaping the character of the congregation who has noble character and is ready to make a positive contribution to the wider community.